PANTOPRAZOLE PHARMACOKINETICS IN OBESITY: WHERE GENES AND SIZE COLLIDE. Issue 1 (14th December 2015) - Shakhnovich, Valentina; Abdel-Rahman, Susan; Friesen, Craig; Pearce, Robin; Gaedigk, Andrea; Leeder, J. Steven; Kearns, Gregory
Abstract : Background: Limited dosing guidelines exist for overweight children (≈30% pediatric population). This prospective study examines the pharmacokinetics (PK) of pantoprazole (CYP2C19 substrate) in overweight vs. normal-weight children. Methods: Using TaqMan techniques, 51 children (6–17 yrs) were genotyped for CYP2C19 loss-of-function ( *2, *3, *4 ) and gain-of-function ( *17 ) alleles. After a single oral dose of pantoprazole (1.2 mg/kg lean body weight), 10 plasma samples were collected over 8hrs, pantoprazole/metabolite concentrations measured by HPLC-UV, and PK parameters generated via non-compartmental methods. Using a two-tailed unpaired t-test, parameters were compared between overweight/obese (n=24) and normal-weight (n=25) children, and the effect of CYP2C19 genotype ( *1/*1, n=24; *1/*17, n=15; *1/*2, n=7; *2/*17, n=3; *2/*2, n=2) on drug disposition was analyzed using a one-way ANOVA; α=0.05. Results: Dose-adjusted AUCtot, CL/F and other PK parameters were not significantly different between overweight/obese and normal-weight children. Independent of weight, mean AUCtot for pantoprazole was 2-fold greater in children with 1 loss-of-function vs. 1 gain-of-function allele (p=0.01). CL/F was increased only in children with *1/*17 genotype compared to all other genotypes (p<0.03), except *2/*17 . In children with *1/*1 genotype (n=24), CL/F was significantly reduced (0.25±0.1 vs. 0.41±0.23 L/h/kg; p<0.05) and AUCtot increased (5.3±3.5 vs. 3.1±1.5 mg*h/L; p=0.05) in overweight/obese vs. normal-weight children. AUCtot was significantly increased in obese vs. normal-weight children (8.1±4.6 vs. 3.1±1.5 mg*h/L; p<0.05), with a positive correlation observed between AUCtot and BMI (r 2 =0.4; p=0.01). Conclusions: CYP2C19 genotype appears to be the primary determinant of pantoprazole PK in children, whereas BMI may explain individual variability within genotype groups.